2021
DOI: 10.1212/wnl.0000000000011893
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Impact of Psychiatric, Cognitive, and Motor Abnormalities in Huntington Disease

Abstract: ObjectiveTo assess the prevalence, timing and functional impact of psychiatric, cognitive and motor abnormalities in Huntington’s disease (HD) gene carriers, we analysed retrospective clinical data from individuals with manifest HD.MethodsClinical features of HD patients were analysed for 6316 individuals in the European REGISTRY study from 161 sites across 17 countries. Data came from clinical history and the patient-completed Clinical Characteristics Questionnaire that assessed eight symptoms: motor, cogniti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 46 publications
(72 reference statements)
4
54
1
6
Order By: Relevance
“…Another equally prevalent symptom in HD is depression. McAllister and colleagues ( 41 ) analyzed the prevalence, timing, and functional impact of psychiatric, cognitive, and motor abnormalities in HD in more than 6,000 individuals from the European Huntington's Disease Network 4 . They found that the most prevalent symptom after motor symptoms was depression, occurring in 64.5% of individuals with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Another equally prevalent symptom in HD is depression. McAllister and colleagues ( 41 ) analyzed the prevalence, timing, and functional impact of psychiatric, cognitive, and motor abnormalities in HD in more than 6,000 individuals from the European Huntington's Disease Network 4 . They found that the most prevalent symptom after motor symptoms was depression, occurring in 64.5% of individuals with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits are reported as initial disease signs in 30%–83% of JHD patients, before motor onset is apparent 8,21,24,25 . This wide range might be attributed to differences in description but emphasizes the notion that cognitive deficits are prominent in the initial stage of JHD.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…For non-motor onsets, or where the clinician's onset estimate was missing, the motor component of the clinical characteristics questionnaire was instead used (ccmtrage; (McAllister et al, 2021)). The Registry population was stratified by residual age at onset and 250 (~ 4%) at each extreme of the distribution selected for analysis (exact samples depending on DNA availability) along with 7 technical exome-sequencing controls of different CAG repeat lengths and residuals of zero.…”
Section: Clinical Sample Selectionmentioning
confidence: 99%